Human Coronaviruses: Genetics, Virulence Factors and Pathophysiology, Diseases’ Epidemiology - Katawa, Gnatoulma; Gambogou, Banfitebiyi; Nguepou, Christèle T.; Ataba, Essoham; Ritter, Manuel; Kamassa, Eya H.; Bara, Fagdéba D.; Karou, Simplice D.; Ameyapoh, Yaovi (International Journal of Innovative Research in Medical Science, 2021)
Coronaviruses are pathogens for both animals and humans. The recent Coronavirus Disease (Covid-19), caused by a novel Coronavirus (SARS-CoV-2), outbreak that took place in Hubei (Wuhan, China) from December 2019 aroused numerous questions regarding the nature and the origin of the SARS-CoV-2. Literature review of the main publications from scientific data bases was undertaken. These data revealed similarities of symptoms and identity of genome with the SARS-CoV. In this review, the genetics and virulence factors of coronaviruses, the disease pathophysiology and epidemiology were examined.